From awareness to action: addressing the underlying factors of the glass ceiling effect for women in multiple sectors / Carolina Novi Mustikarini ... [et al.] - Mustikarini, Carolina Novi; Tanesia, Cindy Yoel; Antonio, Tony; Suade, Yuyun Karystin Meilisa; Syam, Asriah; Sharon, Salmah (2023)
The Glass Ceiling Effect is a phenomenon that portrays intangible obstacles often interfering the career advancement of talented people, especially women, to top-level management positions. This article aims to explore the underlying factors of the Glass Ceiling Effect in Indonesia, with a focus on the career challenges faced by women and the barriers in achieving gender equality in the workplace. The study included 100 female respondents working in various sectors. The research findings show that there are several factors reflecting the Glass Ceiling Effect such as Internal Business Structure, Social Challenges, Situational Challenges, and Individual Challenges. On the other hand, the Government Challenge factor does not reflect the Glass Ceiling Effect.